EDUKASI SEJARAH 4.0: PENGGUNAAN TEKNOLOGI AI DALAM PEMBELAJARAN SEJARAH - Fahruddin (KARMAWIBANGGA: Historical Studies Journal, 2024)
This study aims to develop and evaluate the effectiveness of an Artificial Intelligence (AI)-based history learning model in enhancing the quality and effectiveness of teaching in high schools. The research method used is a quasi-experimental design, dividing students into two groups: an experimental group using AI-based learning and a control group using conventional methods. Data were collected through achievement tests, student perception questionnaires, and interviews with teachers. The results show that students in the experimental group experienced a more significant increase in test scores compared to the control group. Additionally, students using AI-based learning reported higher levels of satisfaction, engagement, and motivation. These findings indicate that AI has great potential to improve student learning outcomes and learning experiences. The global benefits of this study include providing a learning model that can be applied in various countries to enhance the quality of history education, as well as contributing to the development of more inclusive and adaptive educational technologies. Keywords: Artificial intelligence, history learning, learning effectiveness, educational technology